Antibacterial Activity of thanol Extract and Ethylacetate Fraction of Casia Alata Leaf from Kendari-Southeast Sulawesi - Nurlansi Nurlansi; Jahidin Jahidin (Journal of Tropical Pharmacy and Chemistry, 2016)
Active compound extracted from Casia alata leaf was obtained from methanol extract and ethylacetat fraction. Based on research, anti bacteria activity of methanol extract of Casia alata at concentration 6 mg/mL gave high inhibition of the growth of positive gram bacteria colonies of B. cereus and S. aureus with inhibition zone 11,0 mm and 16,1 mm and gaves negative inhibiton of negative gram bacteria colonies of E. coli and S. typhi with inhibition zone 11,6 mm dan 5,9 mm. Ethylasetat fraction showed higher zone inhibition then methanol extract. Based on research result it was show that ethylacetat fraction gaves strong inhibition of the growth of positive gram bacteria colonies of B. cereus and S. aureus with inhibition zone 18,1 mm and 14,3 mm, and gave moderate inhabitation for negative gram bacteria colonies of coli and S. typhi with inhibition zone 9,0 mm and 5,7 mm. Separation result of ethylacetat fraction using coloumn chromatography with silica gel G60 F254 Âas stationary pahase showed that ethylacetat fraction with the same concentration at 6 mg/mL show higher inhibition effect especially for positive gram bacteria colonies of B. cereus and S. aureus with inhibition zone 24,2 mm and 24.0 mm. Key Word: Casia alata, ethylacetat ftaction, antibacteria activity